The Impact of Random Content on TikTok on Youth Behavior - Sharadga, Tahseen Mohammad Anis Hassan (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to identify the impact of random content on TikTok platforms on youth behavior, factors affecting the spread of spam content on TikTok and to identify social and psychological challenges that young people might face as a result of exposure to random content on TikTok. Methods: The survey method was used to achieve the study objective. To conduct the study, the researcher prepared a questionnaire distributed to 28 faculty members from Yarmouk University, Zarqa University, and Middle East University. Results: The results revealed that the impact of random content on TikTok varies between individuals, as some find it entertaining and enjoyable, while others consider it addictive and harmful to their mood. In addition, the results indicated that random content can negatively affect individuals’ mental health by increasing feelings of anxiety and depression. Moreover, the study highlighted that using the TikTok platform can affect individuals’ lifestyles, including their sleep and social relationships with family and friends. Conclusion: The study concluded by emphasizing the urgent need to raise awareness of the importance of improving the content classification system and enhancing content control on TikTok to reduce the spread of random content, in addition to the creation of positive and useful content on TikTok to influence youth behavior.